Hairy root cultures as a multitask platform for green biotechnology - Gerszberg, A.; Wiktorek-Smagur, A.
Hairy root cultures serve as a useful tool in the experiments aiming to understand plant biology (e.g. functional analysis of gene function)which affects their use in biotechnology. Due to their numerous valuable features hairy root cultures provide an economic yet secure platform to produce active biomolecules. Hence, these cultures are mainly exploited to produce secondary metabolites or recombinant proteins for pharmaceutical or industrial applications. Moreover, numerous studies have shown that the discussed cultures are a promising platform for phytoremediation and thus for environmental restoration. This paper is a brief summary of the main achievements in the application of hairy root cultures.
Keywords: HAIRY ROOT; BIOREACTORS; SECONDARY METABOLITES; RECOMBINANT PROTEINS; PHYTOREMEDIATION; AGROBACTERIUM RHIZOGENES